Political confidence and quality of democracy in Brazil (2006-2016): theoretical approach and some empirical data - da Silva, Carolini (Journal Studies of Public Policy, 2019)
The purpose of this paper is to analyze whether there is a relationship between the quality of democracy and political trust in Brazil. To achieve this goal, at first, we rehearsed a point of contact between the literatures and, secondly, we analyzed the performance of political parties, the National Congress and the Judiciary – based on three dimensions of the quality of democracies: rule of law, vertical accountability and horizontal accountability – and we compare it with the level of citizen confidence in these institutions, through a descriptive analysis of data from the latinobarometer (2006-2016). We conclude that political trust and the quality of democracy would be related to the criteria they use to measure institutional performance, that is, the literature promotes a debate about the performance of institutions based on similar criteria, such as the application of the rule of law and vertical and horizontal controls of institutional actors. In Brazil, the quality of institutional performance suggests an interpretation of the fact that the phenomenon of distrust affects to a greater extent representative institutions and to a lesser extent the institutions whose authority comes from the ability to establish controls over political power.